Zastosowanie metod taksonomicznych do oceny konglomeratów finansowych - Michalski, Tomasz; Lewandowski, Artur (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The authors propose an alternative approach to the evaluation of financial conglomerates. This approach is based on the use of taxonomic methods in the building of a system helping financial analysts to initially identify a financial conglomerate with high growth potential. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 260-269